PENGAJARAN MELALUI SIMBOL-SIMBOL DALAM KITAB YEREMIA - Nanik Sutarni (JURNAL PENABIBLOS, 2019)
Jeremiah, a prophet of God who carried out his calling as a prophet by conveying messages received from God. The symbol or symbol used by the prophet Jeremiah in conveying messages that have been received from God, delivered to the recipient: the people of Judah. Three methods of communication were employed: word / verbal, written / printed and gestures, symbols / symbols performed, Jeremiah as a communicator paid attention to who he wanted to convey the message to. As a prophet who brings a message from God is about to bring the people of Judah back to God; Jeremiah warns of the consequences that will occur if they continue to carry out their behavior. They reject the word of God delivered through the prophet. They have abandoned the Lord and worshiped idols, stubbornness and injustice, and improper use of temples and sacrifices. The ten symbols of teaching that are performed are in accordance with the instructions given by God to him